2018
DOI: 10.1016/s1473-3099(18)30245-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, aetiology, and sequelae of viral meningitis in UK adults: a multicentre prospective observational cohort study

Abstract: SummaryBackgroundViral meningitis is increasingly recognised, but little is known about the frequency with which it occurs, or the causes and outcomes in the UK. We aimed to determine the incidence, causes, and sequelae in UK adults to improve the management of patients and assist in health service planning.MethodsWe did a multicentre prospective observational cohort study of adults with suspected meningitis at 42 hospitals across England. Nested within this study, in the National Health Service (NHS) northwes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
155
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(173 citation statements)
references
References 33 publications
11
155
2
5
Order By: Relevance
“…In addition to being time consuming, this approach is often ineffective; no etiology is identified in 60% of patients with encephalitis 92-94 and meningitis. 95 Moreover, the cost of such a workup has been estimated to be up to $10,000 per patient. 96 Therefore, there is considerable interest in broadrange assays that offer the potential to identify multiple pathogens with a single test.…”
Section: Broad-range Diagnostic Testing Approachesmentioning
confidence: 99%
“…In addition to being time consuming, this approach is often ineffective; no etiology is identified in 60% of patients with encephalitis 92-94 and meningitis. 95 Moreover, the cost of such a workup has been estimated to be up to $10,000 per patient. 96 Therefore, there is considerable interest in broadrange assays that offer the potential to identify multiple pathogens with a single test.…”
Section: Broad-range Diagnostic Testing Approachesmentioning
confidence: 99%
“…As a perspective for future research, it would be useful to assess the characteristics of each diagnostic physical examination test after classifying the patients based on the detected meningitis‐causing microorganisms, that is, viruses or bacteria. Because bacterial meningitis is usually more urgent and fatal than viral meningitis, knowing the sensitivity and specificity of each physical examination for each type of the causative microorganism may help clinicians to estimate the risk for bacterial meningitis in the primary care setting. Likewise, subgroup analyses for the characteristics of each physical examination test with variables other than the microorganism, such as disease severity or the level of CSF pleocytosis, would be also important.…”
Section: Discussionmentioning
confidence: 99%
“…8 Some, but not all studies, have shown an increased risk of neurological morbidity after HSV-2 meningitis, [8][9][10] and a recent UK-study found that patients with HSV-2 meningitis had a lower quality of life than healthy controls at one-year follow-up. 2 Studies on long-term outcomes of HSV CNS infections are scarce and often hampered by small or selected study populations restricted to patients with severe HSV encephalitis, patients admitted to referral centers, or patients from a single center, and by lack of adequate comparison cohorts. 5,6,10,11 Follow-up rarely exceeds one year, 12 and no studies have included complete national data on all HSV-1 and HSV-2 CNS infections.…”
Section: Introductionmentioning
confidence: 99%